You can't drink a meatball through a straw - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2016)
Hank's cousin Judith Ann is an excellent cook, and does not let Hank forget it, but when Hank enters a cooking competition with her he finds out that she has trouble in school, just like Hank.